SUSTAINING A SUSTAINABILITY REPORT BY MODIFYING TRIPLE BOTTOM LINE TO PENTAPLE BOTTOM LINE: AN IMAGINARY RESEARCH DIALOGUE - Sukoharsono, Eko Ganis (Accounting Department,, 2019)
The study is an imaginary research dialogue. The dialogue is between two scholars: Senior and Junior Researchers. To bring up their imagination, postmodernism is used to explore the dialogue. Both are trying to discuss the current issues on Sustainability Report Disclosures. The objective of the study is to explicate Sustainability Report Disclosures by modifying Triple Bottom Line to Pentaple Bottom Line. Postmodernism is used to open our minds of research report writings and arguments by using dialogue to introduce Pentaple Bottom Line in Sustainability Report Disclosures.The result of the study is that Pentaple Bottom Line is a mode of comprehensive disclosures on the preparation of sustainability report by any organization either business or public, and either big or small. The Pentaple Bottom Line is 5 Ps: Planet, People, Profit, Phenotechnology and Prophet. Planet means to preserve natural environment as a balance of operational activities of an organizational contribution. People give its meaning that the balance with the welfare of people (internal and external organizations) or the community becomes important to contribute to the corporation. Proportion in providing justice in people's welfare is an effort to be balanced. Profit is an effort that is now dominant in achieving organizational performance must be balanced. Profit or welfare in economic aspects is important, but must be balanced with the other Ps. Phenotechnology is the fact that the existence or phenomenon of information technology must be an important part in maintaining the survival of the corporation. Prophet is a spiritual, mental, or spiritual balance in the process of preserving life of an organization.